The best kept secret of Christian mission : promoting the gospel with more than our lips - Dickson, John, 1951- (Grand Rapids, Mich. : Zondervan, 2010)
In this practical guide to the biblical art of sharing your faith, John Dickson offers refreshing insight into the ways that all Christians can and should be involved in spreading the good news of Jesus. While not all Christians are called and gifted to become evangelists, we are all called to promote the gospel through a wide range of activities--prayer, financial partnership, good deeds, godly lives, public worship, daily conversation, etc.--with and without our lips.
Confessions of an evangelist -- The one and the many: why get involved in mission? -- The many and the one: the challenge of pluralism -- Following the "friend of sinners": the missionary mind of the ordinary Christian -- The hidden mission: promoting the gospel with our prayers -- Partners for life: promoting the gospel with our money -- Being the light of the world: promoting the gospel through the works of the church -- Being beautiful: promoting the gospel through Christian behaviour -- What is the gospel?: the message we promote -- The few and the many: evangelists and the local church -- Heralds together: promoting the gospel through our public praise -- The apt reply: promoting the gospel in daily conversation -- A year in the life of the gospel: bringing it all together -- Appendix 1: gospel bites -- Appendix 2: a modern retelling of the gospel -- .
Includes bibliographical references (p. 219-229) and indexes.
Keywords: Missions; Witness bearing (Christianity)